2019
DOI: 10.21203/rs.2.14296/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Educational roles as a continuum of mentoring’s role in medicine – A systematic review and thematic analysis of educational studies from 2000 to 2018

Abstract: Introduction: Recent studies have gone to great lengths to differentiate mentoring from teaching, tutoring, role modelling, coaching and supervision in efforts to better understand mentoring processes. This review seeks to evaluate the notion that teaching, tutoring, role modelling, coaching and supervision may in fact be part of the mentoring process. To evaluate this theory, this review scrutinizes current literature on teaching, tutoring, role modelling, coaching and supervision to evaluate their commonalit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…This view is reinforced by Alkhawaldeh (2017) who defined mentoring as one-on-one relationship in which an expert or a senior person who is the mentor voluntarily gives time to teach, support, and encourage the trainee teacher. Many authors have suggested various roles of mentors in teaching practice such as fostering pre-service teacher's personal and professional development, and providing support, direction and feedback regarding career plans (Hudson 2017;Krishna et al 2019). However, Maphosa and Ndamba (2012) and Shumba et al (2016), writing from a Zimbabwean context, stated that the role of mentors entails counseling, coaching, guiding, disciplining and advising trainee teachers on pedagogical issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This view is reinforced by Alkhawaldeh (2017) who defined mentoring as one-on-one relationship in which an expert or a senior person who is the mentor voluntarily gives time to teach, support, and encourage the trainee teacher. Many authors have suggested various roles of mentors in teaching practice such as fostering pre-service teacher's personal and professional development, and providing support, direction and feedback regarding career plans (Hudson 2017;Krishna et al 2019). However, Maphosa and Ndamba (2012) and Shumba et al (2016), writing from a Zimbabwean context, stated that the role of mentors entails counseling, coaching, guiding, disciplining and advising trainee teachers on pedagogical issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49] This suggests that peer, near-peer, group, mosaic, network, leadership, patient, youth, family, and e-mentoring should not be mistakenly conflated nor intermixed with preceptorship, supervision, role modeling, and networking which have their own specific approach and role in education and training. 41 Acknowledging mentoring's context specific nature, this review will focus on the role of the host in novice mentoring which is defined as the "dynamic, A systematic scoping review was adopted to identify "the central sources and forms of evidence available" on host organzations. 42 The flexible nature of a scoping review allows systematic extraction, synthesis, 43 and summarizing 44 of actionable and applicable information across a diverse range of study formats and settings.…”
Section: Studying Mentoringmentioning
confidence: 99%
“…42-49 This suggests that peer, near-peer, group, mosaic, network, leadership, patient, youth, family, and e-mentoring should not be mistakenly conflated nor intermixed with preceptorship, supervision, role modeling, and networking which have their own specific approach and role in education and training. 41 Acknowledging mentoring’s context specific nature, this review will focus on the role of the host in novice mentoring which is defined as the “ dynamic, context-dependent, goal-sensitive, mutually beneficial relationship between an experienced clinician and junior clinicians and/or undergraduates focused upon advancing the development of the mentee. ” 50 Novice mentoring is the dominant form of mentoring in medical education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one has to be careful not to merge these practices with mentoring as that could be a source of confusion in conceptualizing mentoring. In this context, mentoring is defined as a ‘dynamic, context dependent, goal sensitive, mutually beneficial relationship between an experienced clinician or basic scientist and junior clinicians and or undergraduates that is focused on advancing the development of the mentee’ 8…”
mentioning
confidence: 99%